Resection versus drainage in the management of patients with AAST-OIS grade IV blunt pancreatic injury: A single trauma centre experience. Issue 1 (January 2022) - Lin, Being-Chuan; Hwang, Tsann-Long
Highlights: In this series, 19 patients with AAST-OIS grade IV blunt pancreatic injury were diagnosed by abdominal CT ( n  = 7), ERP ( n  = 6), and surgery ( n  = 6). Seven patients underwent peripancreatic drainage with or without parenchyma repair, and the other 12 patients underwent pancreatic resection. Overall, 15 patients developed pancreas-related complication, including two deaths with a 68% morbidity rate and an 11% mortality rate. Pancreatic resection is warranted in early grade IV injuries; however, drainage can be an alternative choice in delayed surgery. Peripancreatic drainage alone is not adequate and 86% of our patients required further therapy (pancreatic duct stent, n  = 3; reoperation, n  = 3). Abstract: Introduction: We aimed to compare outcomes of pancreatic resection with that of peripancreatic drainage for American Association for the Surgery of Trauma–Organ Injury Scale (AAST-OIS) grade IV blunt pancreatic injury in order to determine the optimal treatment method. Materials and methods: Nineteen surgical patients with AAST-OIS grade IV blunt pancreatic injury between 1994 and 2016 were retrospectively studied. Results: Among the 19 patients, 14 were men and 5 were women (median age: 33 years). Twelve patients underwent pancreatic resection (spleen-sacrificing distal pancreatectomy, n  = 6; spleen-preserving distal pancreatectomy, n  = 3; and central pancreatectomy with Roux-en-Y anastomosis, n  = 3), and seven underwent peripancreatic drainage. After comparing these two groups, no significant differences were found in terms of gender, shock at triage, laboratory data, injury severity score, associated injury, length of hospital stay, and complication. The only significant difference was that in the drainage group, the duration from injury to surgery was longer than that from injury to resection (median, 48 hours vs. 24 hours; P  = 0.036). In the drainage group, three patients required reoperation, and another three required further pancreatic duct stent therapy. Conclusions: In the surgery of the grade IV blunt pancreatic injury, pancreatic resection is warranted in early, conclusive MPD injury; if surgery is delayed or MPD injury has not been clearly assessed, peripancreatic drainage is an alternative method. However, peripancreatic drainage alone is not adequate and further pancreatic duct stent or reoperation is required. Further studies should be conducted to confirm our conclusions.